A new blind algorithm for channel estimation in OFDM-based amplify-and-forward two-way relay networks - Tzu-Chiao Lin; See-May Phoong (EURASIP Journal on Wireless Communications and Networking, 2018)
Abstract In this paper, we propose a blind channel estimation algorithm for the amplify-and-forward (AF) two-way relay network (TWRN) which consists of two terminal nodes and one relay node. The orthogonal frequency division multiplexing (OFDM) modulation is adopted for frequency selective channel. Both cyclic prefix (CP) and zero padding (ZP) are considered. The two cascaded channels are estimated in two steps. First, the cascaded channel causing the self-interference is estimated using a proposed power reduction method. Then, the other cascaded channel from source to destination is estimated by subspace method. Closed-form formulas for channel estimates are derived. In addition, we also carry out the theoretical mean square error analysis and derive the approximated Cramer-Rao bounds.